Trade, energy, and carbon dioxide: An analysis for the two economies of Ireland - Marie Hyland; Anne Jennings; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2012)
In this paper we use a subsystem input-output decomposition analysis to examine the drivers of greenhouse gas emissions in the Republic of Ireland and in Northern Ireland. We use a bi-regional input-output analysis to look at how greenhouse gases in one region can be emitted as a result of demand in an exporting region. Looking at emissions generated throughout the island of Ireland, we find that emissions driven by demand in Northern Ireland are larger than those it generates, and vice-versa for the Republic of Ireland. We then use the input-output tables to simulate the effect of imposing a exteuro15/tonne carbon tax in the Republic of Ireland. We find that this causes a decrease in final demand in the Republic of Ireland, and a decrease in output in both the Republic of Ireland and in Northern Ireland; the decrease is greater in the Republic as the domestically produced share of inputs is much larger than the imported share in all sectors.
Keywords: 330; Greenhouse gas emissions; Bi-regional input-output analysis; Carbon tax; Republic of Ireland; Northern Ireland